Genome-wide dissection of genes shaping inflorescence morphology in 242 Chinese south–north sorghum accessions - Guihua Zou; Yanqing Ding; Jianxia Xu; Zhou Feng; Ning Cao; Heyun Chen; Heqin Liu; Xueqiang Zheng; Xiuhui Liu; Liyi Zhang (Scientific Reports)
Abstract The inflorescences morphology (IM) of sorghum (Sorghum bicolor L. Moench) affects its resistance to pests, diseases, and grain yields. However, the specific genetic factors underlying in IM are not yet fully elucidated. Here we conducted a comprehensive genome-wide association analysis (GWAS) to identify the stable and adaptive Quantitative Trait Loci (QTL) for five IM traits (panicle length, the number of cob nodes, the number of primary branches, the largest length of the primary branch, and panicle type) in a sorghum panel, which adapted to different environments from the south to north in China. Totally, 2,015,850 high quality single nucleotide polymorphisms (SNPs) were obtained. Population structure analysis showed that two distinct genetic sub-populations were divided according to their geographic origin. Seventy-one QTLs distributed in 41 genetic regions on 9 chromosomes were identified. These regions harbored 21 high-confident candidate genes that were homologous to rice domestication genes, including 7 related to IM. Two domestication-related genes (Sobic.003G052700 and Sobic.006G247700) were located into two major QTL regions (QTL3.4721839 and QTL6.58709500) which were identified in multi-environments. Allelic variations in the two genes displayed a geographical pattern, indicating that different IM traits were selected by south and north sorghum breeders, such as south sorghums had long and loose panicles in order to adapt the hot and humid climate, while north sorghums had short and compact panicle to increase planting density and grain yield per unit area due to dry climate. This work provides new breeding strategies and resources for developing locally adapted sorghum varieties.